Technical Report: Observations and reanalyses data: comparison and trends in Southeast Asia - Washington, R.; Pearce, H; Engelstaedter, S; Diep, T.K. (CGIAR Research Program on Climate Change, Agriculture and Food Security, 2014)
Reanalyses data sets, being temporally and spatially complete and available on six hourly timescales, are extremely convenient to use. Real observations represent the climate system with greater fidelity than reanalyses can, given that the latter are a complicated blend of observations and models via an assimilation scheme and rely heavily on the assimilation scheme where observations are absent. Knowing whether the reanalyses data reflects real data can be difficult to establish. In this part of the report, the observed data is compared with three reanalyses data sets for the SE Asia region. We use observations from SYNOP and METAR reports. SYNOP and METAR data are, in effect, observations taken at met stations and delivered to the Global Telecommunication System (GTS). Once in the GTS, they can be archived by institutions such as those delivering weather forecasts. Access to these data via the archives is generally much easier than through the individual Met Agencies. This is particularly true in the case of a study covering multiple nation states. These datasets are described in more detail in Sections 1.1 and 1.2.